Bi2Ti2O7‐based pyrochlore nanoparticles and their superior photocatalytic activity under visible light. Issue 1 (5th September 2017) - Benčina, Metka; Valant, Matjaz
Abstract: Nanoparticles of Bi2 Ti2 O7 pyrochlore were synthesized by a coprecipitation method. They exhibit a high visible‐light photoactivity for decolorization of a methyl‐orange dye solution in the presence of a sacrificial agent, H2 O2 . The same pyrochlore system with an Ag co‐catalyst showed even faster kinetics under only visible light and an unprecedentedly high photoactivity in the UV range.